2021
DOI: 10.2147/ijn.s323033
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Loaded-Mesoporous Hydroxylapatite/ Chitosan Therapeutic Scaffolds Regulate Bone Regeneration Ability by Promoting the M2-Type Polarization of Macrophages

Abstract: Purpose Mesoporous hydroxylapatite (MHAP) might be important for bone regeneration, and ursolic acid (UA) has anti-inflammatory effects. Accordingly, we developed, for the first time, ursolic acid-loaded MHAP-chitosan (MHAP-CS-UA) scaffolds to treat bone defects. Methods In vitro, we synthesize biomaterial scaffolds. By SEM, XRD, EDS and FTIR, we test the performance of the hybrid scaffolds. By drug release, flow cytometry, immunofluorescence, alizarin red staining, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The scanning resolution of micro-CT was available in 12 studies, with no more than 20 μm in most of them (11/12). The maximum and minimum resolutions were 28 and 9 μm, respectively ( Zhou et al, 2017 ; Yu et al, 2021 ). Moreover, the scanning tube voltage was reported in 11 literature studies, with no greater than 65 kV in 75% (7/11) of them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scanning resolution of micro-CT was available in 12 studies, with no more than 20 μm in most of them (11/12). The maximum and minimum resolutions were 28 and 9 μm, respectively ( Zhou et al, 2017 ; Yu et al, 2021 ). Moreover, the scanning tube voltage was reported in 11 literature studies, with no greater than 65 kV in 75% (7/11) of them.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 studies reported the freezing temperature, with six of them adopting -20 °C ( Ji et al, 2017 ; Sun et al, 2017 ; Hu et al, 2018 ; Liao et al, 2019 ; Peng et al, 2019 ; Yu et al, 2021 ) and two using −80 °C ( Li Y. et al, 2018 ; Wu T. et al, 2020 ). The scaffolds obtained in the former six studies had mean sizes of about 200 μm, scored as 4–5 points by our semi-quantitative evaluating system for their in vivo studies, while the latter two studies fabricated scaffolds with 100 μm pores and were judged as 3–4 points.…”
Section: Discussionmentioning
confidence: 99%
“…Ursolic acid is an active compound found in a variety of natural plants, which when loaded on biomaterial scaffolds has been shown to enhance bone regeneration by increasing the ALP activity and osteogenic differentiation-related protein and gene expression [ 58 ]. Otherwise, ursolic acid-loaded-mesoporous hydroxylapatite-chitosan scaffolds were reported to regulate bone regeneration ability by inhibiting the polarization of macrophages to M1 type [ 59 ]. In another study, grape seed, pomegranate peel, and jabuticaba peel extracts direct blend with scaffolds of nanohydroxyapatite and collagen showed potent anti-bacterial activity and offered a promising strategy to design novel biomaterials for bone tissue regeneration [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HA-CS-UA scaffolds had good anti-inflammatory, osseointegration, osteo-inductivity, and bone regeneration. [124] Although numerous mineralized CS scaffolds with low biotoxicity and good bioosteogenic effects had been developed in recent years, a lack of standardized study protocols and approaches make it a challenge to compare different study outcomes and promote the further development of mineralized CS scaffolds for BTE. The composition and preparation methods of the composite scaffolds will have different effects on the mechanical properties, biotoxicity, degradability, and bone promotion of the scaffolds.…”
Section: None Nonementioning
confidence: 99%